Research of Bump Detection Method of Spiral Bevel Gear Tooth Surface based on Gear Contact Analysis - Xia Hepeng; Deng Xiaozhong; Xu Aijun; Liu Saisai (Jixie chuandong)
A detection method of gear tooth flank bump is presented,which is used to determine the position of bump surface of spiral bevel gear. A meshing model of hypoid gear pair is established,and the V,H,J adjustment is solved by changing the offset of the contact zone to obtain the position of the TCA contact zone under the planned path. The V,H,J calculation result is used to guide the rolling inspection experiment. In YX-HTT600 gear error measurement and analysis of comprehensive testing machine rolling test,the transmission error measurement results of the two cases of hypoid gear pair normal tooth surface and the existence of bump tooth surface are got. By comparing the measurement results of the two kinds of transmission errors,the feasibility of the proposed tooth surface measurement method is verified. The experimental results show that the proposed tooth surface detection method can be used to detect the entire tooth surface of spiral bevel gears. The test results can reflect the position of the bump surface and the number of the tooth surface with bumping points,which can lay a foundation for further improving the meshing performance of the spiral bevel gear basis.